Novel Colorimetric Determination of Phytate in Urine. (22nd January 2016) - Berga, Francisco; Rodriguez, Adrian; Costa-Bauzá, Antonia; Grases, Félix
ABSTRACT: Phytate is a natural substance present in urine and biological fluids that is associated with health benefits. Existing methods for the determination of phytate are not applicable to routine measurements in urine by clinical laboratories. This study describes a new method for measuring urinary phytate. Following its purification and preconcentration from urine by solid-phase extraction, phytate may be determined colorimetrically using Al(III)-lumogallion or Al(III)-pyrocatechol violet. Following preconcentration, the Al(III)-lumogallion assay was linear for 0 to 15 µM phytate with a limit of detection of 0.183 µM. In contrast, the Al(III)-pyrocatechol violet system was linear with phytate concentration from 0 to 10 µM and provided a limit of detection of 0.010 µM with a preconcentration procedure. Both methods are simple, rapid, accurate, reliable, and sensitive. Comparisons using synthetic and human urine samples with a reference Al(III)-xylenol orange method showed that the Al(III)-pyrocatechol violet assay is a good alternative for measuring urinary phytate.